PEMBERITAAN MEDIA ASING MENGENAI HUKUM CAMBUK GAY DI ACEH - Reni Juliani (SOURCE : Jurnal Ilmu Komunikasi, 2017)
This study aims to analyze why there are pro and cons of foreign media in the news of the whippingof gay couples in Aceh. The method used in this research is qualitative method. The subjects ofthis research are some sources of news from media. Data collection techniques were conductedwith library research and documentation. The results obtained after conducting library researchand documentation are two issues that make the media pro and cons against the news of this case.The first is the issue of caning and human right law, and the second is the gay issue of minorities.Pro-gay and anti-Islam stigma are built on the issue of human right violstions and caningpunishmant that considered other forms of torture in various reports.Keywords: News, Foreign Media, Caning Law, and Gay.